Sgarbossa Criteria in Left Bundle Branch Block in a Hypertensive Emergency, a Case Report - Sayed,Yaser Mohammed Hassanain El (2021)
Abstract Left bundle branch block and hypertensive emergency are very common conditions in clinical cardiovascular and emergency practice. Hypertensive emergency encompasses a spectrum of clinical presentations in which uncontrolled blood pressure leads to progressive end-organ dysfunction. Suspected acute myocardial infarction in the setting of a left bundle branch block presents a unique diagnostic and therapeutic challenge to the clinician. The diagnosis is especially difficult due to electrocardiographic changes caused by altered ventricular depolarization. However, reports on the use of the Sgarbossa’s criteria during the management of hypertensive emergency are rare. My current case is a hypertensive emergency patient with acute chest pain and left bundle branch block. Sgarbossa’s criteria were initially very weak and, over time, became highly suggestive of acute ST-segment elevation myocardial infarction. Interestingly, chest pain increased as the Sgarbossa’s diagnostic criteria were met. Here, we present a case of developing ST-segment elevation myocardial infarction with left bundle branch block that is indicating for thrombolytic therapy. Thrombolytic therapy was strongly indicated because of a higher developing of Sgarbossa criteria scoring. Thus, the higher Sgarbossa criteria scoring in the case was the only indication for thrombolytic. Therefore, how did Sgarbossa criteria developing during the course of the case to indicating the need for thrombolytic therapy?